Bovine leukocyte antigen major histocompatibility complex class II DRB3*2703 and DRB3*1501 alleles are associated with variation in levels of protection against Theileria parva challenge following immunization with the sporozoite p67 antigen - Ballingall, Keith T.; Luyai, A.; Rowlands, G.J.; Sales, J.; Musoke, A.J.; Morzaria, S.P.; McKeever, Declan J. (American Society for Microbiology, 2004)
Initial laboratory trials of an experimental subunit vaccine against Theileria parva based on the 67-kDa major sporozoite surface antigen revealed a range of responses to challenge. We have analyzed convergence in seven sets of monozygotic twins which suggests that genetic factors may have an influence in determining the degree of protection provided by p67 immunization. In addition, we have examined whether allelic diversity at major histocompatibility complex class II loci influences protection. Analysis of bovine leukocyte antigen DRB3 diversity in 201 animals identified significant associations with vaccine success (DRB3*2703; P = 0.027) and vaccine failure (DRB3*1501; P = 0.013). Furthermore, DRB3*2703 was associated with the likelihood of immunized animals showing little to no clinical signs of disease following challenge. We discuss the acquired and innate immune mechanisms that may be behind the associations described here.